SARS-CoV-2 Antibody Prevalence in the Portuguese Municipality of Vila Nova de Gaia after the First Wave of the Pandemic - de Carvalho, Álvaro (2022)
Introduction: Assessment of SARS-CoV-2 seroprevalence may detect the real spread of the virus because antibody data can provide a long-lasting measure of infection. Existing serological studies in Portugal have tested new serology methods, albeit with small sample sizes and a lack the focus on geographical regions with a high rate of infection cases. The aim of this study was to estimate the serological prevalence of SARS-CoV-2 in Vila Nova de Gaia, the most populous municipality in the north of Portugal and one of those most affected during the first pandemic wave.Material and Methods: A cross-sectional observational study was conducted between June 23rd and July 17th, 2020. Included in the cohort were 18- to 74-year-old men and women living in the municipality of Vila Nova de Gaia, who were sampled through a nonprobabilistic quota-based approach. Cases with a previous RT-PCR diagnosis of COVID-19 were excluded. Sociodemographic and clinical information was collected using a self-administered, written questionnaire. Blood samples were collected for serological laboratory analysis to detect and quantify SARS-CoV-2 anti-IgG antibodies.Results: We tested 2754 participants. Our results show a SARS-CoV-2 seroprevalence of 3.03% (95% confidence interval: 2.37% – 3.87%). Being a smoker (odds ratio: 0.382, 95% confidence interval: 0.147 – 0.99) and having symptoms of COVID-19 (odds ratio: 2.480, 95% confidence interval: 1.360 – 4.522) were consistently associated with lower and higher odds of SARS-CoV-2 antibody presence, respectively, regardless of the analytic design. Moreover, without adjusting for any variables, having had contact with an infected person within the household was associated with increased odds of a positive test (odds ratio: 9.684, 95% confidence interval: 4.06 – 23.101); after adjusting, having self-reported chronic diseases (odds ratio: 0.448, 95% confidence interval: 0.213 – 0.941) was associated with decreased odds.Conclusion: This was the first study to estimate the serological prevalence of SARS-CoV-2 in one of the most populous municipalities in Portugal, representing the first step in the development of an epidemiological surveillance system in Portugal, which can help to improve the diagnosis of COVID-19.